Application of statistically simplex-centroid mixture design to optimize the TPC and TFC on the proportion of polyherbal formulation used by jakun women - Ismail, Nur Amalina; Abu Bakar, Mohd Fadzelly; Kormin, Faridah; Alona C., Linatoc; Mohamed, Maryati (Medwell Publisers, 2018)
The objectives of this study were to model the extraction of Total Phenolic (TPC) and Flavonoid Content (TFC) from mixtures of Cnestis palala, Urceola micrantha, Labisia pumila and Microporus xanthopus and to determine the optimal formulation of the herbal mixture. The dried plant materials were extracted using hot boiling water extraction procedure. Samples (0.1 g) were infused in 200 mL boiling distilled water (100°C), stirred for 3 min using a magnetic stirrer, left to cool for 5 min and filtered using filter paper. Folin-Ciocalteu method and aluminium colorimetric method were used for measurement of TPC and TFC. About 24 formulations of herbal mixture were generated by using Design-Expert 9.0 Software. Quadratic and linear model were found to be the best model for describing the relationship between the proportion of polyherbs with the TPC and TFC. The optimal formulations were validate experimentally. The highest TPC and TFC were shown by single formulation of C. palala. The experiments reported in current study demonstrated that the application of statistical mixture design is an efficient tool to analyse the optimal formulation of herbal mixture.